PERANCANGAN SISTEM KANBAN BARCODE PADA AREA WAREHOUSE (STUDI KASUS : PT.SPIB) - Rini Octaviani Santosa; Vera Methalina Afma; Abdullah Merjani (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2022)
PT. SPIB is one of plastic manufacturer components in Batam. In the process of recording transactions of goods entering the warehouse or called GTN  (Goods Transfer Notes) manually, there is the potential for recording errors to occur, causing data discrepancies between report data and actual goods. Based on data in June 2021 with a GTN frequency of 1,734 times, there Stock Errors were 108 times. The design of the Kanban System Barcode in this study aims to reduce the problems that occur in the transaction process of goods entering the warehouse. The results of using the kanban system barcode method, show a decrease in Stock Error to 14 times with GTN data in July 2021 as many as 1,161 times. And percentage data Stock Error in June amounted to 89% down to 11% in July. In addition, there is a decrease in working time on the process flow map from 43 minutes to 23 minutes and can reduce repetitive work processes in the GTN process.